Children with cancer: a survey on the experience of Italian primary care pediatricians. - Minute, Marta; Cozzi, Giorgio; Plotti, Chiara; Montanari, Giuseppe; Pecile, Paolo; Zanazzo, Giulio Andrea; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2017)
BACKGROUND: Cancer is the second cause of death in children and its diagnosis can be difficult, due to the presence of vague and non-specific symptoms. The primary care pediatrician is often involved in the diagnostic process, but no longer in child care once the treatment started. Care models involving both primary care pediatricians and oncologic referral centre highlighted a higher family satisfaction when they worked together. We conducted a survey on primary care pediatricians involved in childhood cancer in order to describe the actual situation. METHODS: We conducted a retrospective survey enrolling primary care pediatricians from a north-eastern area of Italy. They received a questionnaire that consisted in two parts: the first one aimed to assess the physician's seniority and experience and the second one pertained to each case of cancer and explored the relationship between the pediatrician, the family and the referral centre, and pediatricians degree of satisfaction and emotional impact. RESULTS: We obtained data from 79 pediatricians who described 150 cancer cases. In 99 cases the primary care pediatrician had visited the child at the onset of symptoms and had referred him to the hospital. In 89 cases, he understood the severity of the disease. In 53.3% of cases the pediatrician was informed by the referral centre. The relationship between the pediatrician and child's family improved in 38% of cases and this was related with their participation to the multidisciplinary meetings on child health. CONCLUSIONS: Primary pediatricians' sharing in the management of their patients with cancer was not satisfactory. Development of specific protocols targeted to an integrated care is needed to increase primary pediatricians' involvement and families' satisfactions.
Keywords: Child; Child, Preschool; Cross-Sectional Studies; Disease-Free Survival; Female; Humans; Italy; Male; Needs Assessment; Neoplasms; Outcome Assessment (Health Care); Pediatricians; Practice Patterns, Physicians'; Prevalence; Primary Health Care; Retrospective Studies; Risk Assessment; Survival Analysis